Hepatocyte polyploidization and its association with pathophysiological processes - Wang, Min-Jun (Cell Death Dis, 2017)
A characteristic cellular feature of the mammalian liver is the progressive polyploidization of the hepatocytes, where individual cells acquire more than two sets of chromosomes. Polyploidization results from cytokinesis failure that takes place progressively during the course of postnatal development. The proportion of polyploidy also increases with the aging process or with cellular stress such as surgical resection, toxic stimulation, metabolic overload, or oxidative damage, to involve as much as 90% of the hepatocytes in mice and 40% in humans. Hepatocyte polyploidization is generally considered an indicator of terminal differentiation and cellular senescence, and related to the dysfunction of insulin and p53/p21 signaling pathways. Interestingly, the high prevalence of hepatocyte polyploidization in the aged mouse liver can be reversed when the senescent hepatocytes are serially transplanted into young mouse livers. Here we review the current knowledge on the mechanism of hepatocytes polyploidization during postnatal growth, aging, and liver diseases. The biologic significance of polyploidization in senescent reversal, within the context of new ways to think of liver aging and liver diseases is considered.